2020
DOI: 10.1515/almed-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Towards personalized prostate cancer screening

Abstract: The value of the prostate-specific antigen (PSA) in prostate cancer (PCa) screening is controversial. Contradictory results have been reported in the literature as to whether PSA-based screening reduces mortality. Also, some of the studies published are methodologically flawed. However, evidence consistently demonstrates that screening programs results in the identification of patients with indolent prostatic tumors which rate has increased.Controversy is not only about the value of PSA-based screening, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In addition, the possible positive outcomes of screening are no greater than the adverse outcomes of excessive detection and unnecessary treatment [13]. Diagnosis of PCa based only on PSA levels is therefore gradually losing its appeal as a clinical approach [14]; however, this has not put an end to the controversy surrounding screening [15,16]. A recent study suggested that although discontinuation of PSA-based screening would eliminate excessive diagnoses, the lack of screening would lead to a complete failure to avoid preventable deaths and would increase the PCa-related mortality rate by 13-20% [17].…”
Section: Overviewmentioning
confidence: 99%
“…In addition, the possible positive outcomes of screening are no greater than the adverse outcomes of excessive detection and unnecessary treatment [13]. Diagnosis of PCa based only on PSA levels is therefore gradually losing its appeal as a clinical approach [14]; however, this has not put an end to the controversy surrounding screening [15,16]. A recent study suggested that although discontinuation of PSA-based screening would eliminate excessive diagnoses, the lack of screening would lead to a complete failure to avoid preventable deaths and would increase the PCa-related mortality rate by 13-20% [17].…”
Section: Overviewmentioning
confidence: 99%
“…However, circumstantial evidence confirmed that, in both women and men, other tissues and organs express PSA (Dash, 2015 ; Eklund et al., 2017 ; Musrap & Diamandis, 2016 ; Pérez‐Ibave et al., 2018 ). Now, it is widely accepted that PSA is not prostate‐specific (Mashkoor et al., 2013 ); hence, its screening utility has been questioned (Filella, 2020 ; Gandaglia et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These epidemiological parameters regarding PC have undergone significant changes, especially after the introduction of prostate-specific antigen (PSA) screening and prostate tissue biopsy in current medical practice. The use of PSA testing in the general population, concurring with easier access to improved medical services and increased life expectancy could explain the ascending trend of the overall incidence accompanied by a minimal decrease of the mortality rate, but also, could be responsible for overdiagnosis and overtreatment of 22% up to 67% of the newly indolent PC cases [ 3 , 4 ]. Facing this controversial screening procedure, numerous efforts have been directed in identifying novel, more precise methods of detection and improvement of patient selection in PC screening.…”
Section: ⧉ Introductionmentioning
confidence: 99%